Detection of group B streptococcus colonization in cervical and lower vaginal secretions of pregnant women - Y.X. Wang; M. Zhong; H. Yi; H.F. He (IMR Press, 2020)
Objective: To examine the efficacy of cervical and lower vaginal secretions in the detection of group B streptococcus (GBS) colonization in women in early and late pregnancy. Materials and Methods: Two-thousand women in early pregnancy (8-12 weeks of gestation) aged approximately 27 years who visited our outpatient clinic from December 2016 to December 2018 were enrolled. Cervical and lower vaginal secretions were obtained at 8-12 weeks (early pregnancy) and then at 37 weeks (late pregnancy) of gestation and screened for GBS infection. Patients were classified as follows: (i) cervical and lower vaginal secretions were GBS-positive (group A), (ii) only cervical secretions were GBS-positive (group B), (iii) only lower vaginal secretions were GBS-positive (group C), and (iv) both cervical and lower vaginal secretions were GBS-negative (group D). Results: No difference in the GBS-positive rate was observed between women in early and late pregnancy. The GBS-positive detection rate was lower in women from which cervical secretions were screened than that in women from which lower vaginal secretions were assayed; however, the incidence rates of adverse pregnancy events, such as abortion, preterm delivery, premature rupture of membranes and neonatal infection, were higher in women in which cervical secretions were assayed. Conclusion: Women in early pregnancy should be screened for GBS infection using cervical secretions.